Solving Multiobjective Environmentally Friendly and Economically Feasible Electric Power Distribution Problem by Primal-Dual Interior-Point Method - Jauny; Ghosh D.; Upadhayay A. (My University, 2025)
This paper introduces a primal-dual interior-point algorithm to obtain the Pareto optimal solutions for a multiobjective environmentally friendly and economically feasible distribution problem. This problem has two conflicting objectives—the fuel cost and the emission. A Pascoletti–Serafini scalarization technique is utilized to convert the multiobjective environmentally friendly and economically feasible distribution problem into a parametric scalar optimization problem. We derive the KKT conditions corresponding to the barrier problem of the parametric scalar optimization problem and solve it with the help of primal-dual interior-point method. In order to solve the KKT conditions, the primal-dual interior-point method uses the Newton method to calculate the direction. A merit function is also utilized to take the suitable steplength toward the direction. Successful numerical results of the multiobjective environmentally friendly and economically feasible distribution problem demonstrate the efficiency of the proposed method. © 2023, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.